The Effects of Tokopedia Promoted Product on Indonesia Marketplace Customers - Aziz, H A; Sya’roni, D A W (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
This study aims to discuss the effects of promoted products that usually takes up top spot in Tokopedia search results, how it affects consumer behaviour and purchasing decision. This study uses quantitative methods with questionnaire research as the instruments. Respondents chosen are people who use Tokopedia as their daily online marketplace. This study results conclude that promoted product can increase sales of these promoted products alongside of its seller popularity, branding strategy and products sales, but customer’s purchasing decision of promoted products are also supported by other aspects of products such as convenience of delivery, safety of transactions and then followed by buyer’s reviews. The conclusion found is that promoted product is a good marketing strategy for seller especially if they choose to advertise their high value products. It is hoped that this study can impact seller in Tokopedia to improve their strategy of advertising their products using Tokopedia’s promoted product service, in order to get more sales, better brand recognition and understand more about consumer’s perception of their products without paying unnecessary high advertisement cost.